Potential serum of lactic acid bacteria in horticultural community service entrepreneurs LKSA Widhya Asih, Blimbingsari Village Tourism Area, Jembrana Bali - Ni Ketut Wiradnyani; I Nengah Rata Artana; I Wayan Susrama; Ni Made Rai Erawati (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This paper explores the service to the horticultural community of LKSA Widhya Asih Blimbingsari located in the developing Blimbingsari Digital Tourism Village area, in the State district of Bali. Tells about the development of the community service program for empowering pre-adolescents and LKSA staff Widhy Asih Blimbingsari through the manufacture of fermented products and their derivatives based on rice washing water waste by the Dhyana Pura University team. This project has stimulated the home industry entrepreneurship movement among staff and pre-teens in the LKSA Widhya Asih Blimbingsari community. Using a logical framework in analyzing the steps in an effort to empower existing human resources through kitchen waste, horticulture and fermentation products from rice washing water waste, potentially supporting Blimbingsari tourism, this paper discusses the gap between the problems faced by LKSA Whidhya Asih in terms of kitchen waste. with the prolonged Covid-19 pandemic condition, as a long-term desired anticipation, then describes the activities taken followed by the outputs produced and the results achieved from the implementation of the program, and notes some real impacts that have occurred in the LKSA Widhya Asih Blimbingsari community since its inception program.